ANALISIS KEBUTUHAN DAN KEBIJAKAN SELEKSI PADA PROSES PENGEMBANGAN KOLEKSI AUDIOBOOK DI PERPUSTAKAAN BRAILLE SENTRA WYATA GUNA - Putri, Anneke; Sukaesih; Saepudin, Encang (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
The Braille Sentra Wyata Guna Library plays a crucial role in providing literacy services by offering information access to individuals with visual impairments. This study aims to identify how the implementation of needs analysis and selection policies is carried out in the development of audiobook collections at the Braille Sentra Wyata Guna Library. This research employs a qualitative methodology with a case study approach. Data for this study were gathered through documentation, interviews, observations, and literature review related to the research topic. The findings indicate that the library has made significant efforts in collection development through a needs analysis process involving users, institutions, and related organizations. This analysis is conducted through monitoring and evaluation, as well as direct feedback to ensure that the produced collection is relevant and meets the needs of individuals with visual impairments. The collection selection policy at this library is based on the Rencana Kebutuhan dan Anggaran (RKA), which is developed from the results of monitoring and evaluation and inputs from various parties. This policy provides guidance in determining the types and quantities of collections produced to meet the diverse needs of users.